Immunogenetics - Rezaei, Nima (IntechOpen, 2019)
Because genetic factors can impact immune responses, and immunogenetic associations serve as a predictor of disease development and as a biological indicator of disease progression, the study of immunogenetics is important to basic genetics and immunology, as well as to translational and individualized medicine.This book addresses a few but important issues on the subject of immunogenetics. First, it will review the role that human leukocyte antigen molecules play in the immune system and then take into consideration the effectiveness of Western blotting for the detection of immunologic proteins. The book will discuss studies on the immunogenetics of cancer and tuberculosis followed by implications for immunotherapy. Working separately, the book will also provide evidence that the application of immunogenetics has improved our understanding of brain and behavior disorders.